The Multiple Sclerosis Functional Composite and Symbol Digit Modalities Test as outcome measures in pediatric multiple sclerosis. Issue 2 (April 2019) - Brenton, J. Nicholas; Koshiya, Hitoshi; Woolbright, Emma; Goldman, Myla D.
Background: There is an increasing number of pediatric multiple sclerosis (MS) clinical trials occurring; however, data validating outcome metrics that accurately capture functional disability within pediatric cohorts are limited. Objective: The aim of this study was to investigate the ability of the MS Functional Composite (MSFC) and Symbol Digit Modalities Test (SDMT) to distinguish functional disability in pediatric MS patients. Methods: A total of 20 pediatric MS patients and 40 age and sex-matched controls completed the SDMT and MSFC components: a timed 25-foot walk (T25FW); 9-hole peg test (9HPT); and paced auditory serial addition test (PASAT). Z scores for MS patients were created for each test based on control means. MS patients underwent Expanded Disability Status Scale (EDSS) examination. Results: Pediatric MS patients exhibited low levels of disability on EDSS, median [range]: 1.5 [1.0–3.0]. Compared with controls, MS patients performed significantly lower on SDMT ( p  = 0.0002) and all MSFC components: T25FW ( p  = 0.001), 9HPT ( p  = 0.01), and PASAT ( p  = 0.004). SDMT and MSFC performance were not correlated with EDSS. Conclusions: Despite low levels of neurologic disability as measured by EDSS, pediatric patients with MS exhibit impaired performance in leg function, upper limb fine motor function, and auditory/visuospatial processing speeds, supporting the value of the MSFC and SDMT in this population. Longitudinal studies are needed to further validate their utility.